War & genocide : a concise history of the Holocaust a concise history of the Holocaust - Bergen, Doris L. (Lanham, Md. : Rowman & Littlefield Publishers, 2009)
"In examining one of the defining events of the 20th century, Doris Bergen situates the Holocaust in its historical, political, social, cultural, and military contexts. Unlike many other treatments of the Holocaust, this revised, second edition discusses not only the persecution of the Jews, but also other segments of society victimized by the Nazis: Gypsies, homosexuals, Poles, Soviet POWs, the handicapped, and other groups deemed undesirable. With clear and eloquent prose, Bergen explores the two interconnected goals that drove the Nazi program of conquest and genocide - purification of the so-called Aryan race and expansion of its living space - and discusses how these goals affected the course of World War II."--Jacket.
Preface: War and genocide: race and space -- Preconditions: antisemitism, racism, and common prejudices in early-twentieth-century Europe -- Leadership and will: Adolf Hitler, the National Socialist German Workers' Party, and Nazi ideology -- From revolution to routine: Nazi Germany, 1933-1938 -- Open aggression: in search of war, 1938-1939 -- Experiments in brutality, 1939-1940: war against Poland and the so-called euthanasia program -- Expansion and systematization: exporting war and terror, 1940-1941 -- The peak years of killing: 1942 and 1943 -- Death throes and killing frenzies, 1944-1945 -- Conclusions: The legacies of atrocity.
Includes bibliographical references (p. 245-258) and index.
Keywords: 1900 - 1999; National socialism; Antisemitism -- Germany -- History -- 20th century; Holocaust, Jewish (1939-1945) -- Causes; World War, 1939-1945 -- Causes; Antisemitism; National socialism; War -- Causes; Germany -- History -- 1933-1945.; Germany; History